Tawhidic epistemology: finding “The One in the many” in Greek and Islamic philosophy - Moris, Megawati (Department of Communication, Kulliyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS)., 2025)
Abstract: This article explores the concept of Tawhidic epistemology, which seeks to understand the unity of reality, "The One in the many," through the lens of Greek and Islamic philosophy. ​ It delves into the historical perspectives of early Greek philosophers, such as Thales, Pythagoras, Plato, and Aristotle, and their metaphysical principles of unity and permanence, which influenced Muslim philosophers. The Islamic concept of tawḥīd (oneness of Allah) is presented as the ultimate truth and reality, aligning with the Greek notion of the Primordial Principle. ​ Tawhidic epistemology emphasizes the integration of objective and subjective realms, aiming to discover the oneness of existence amidst the diversity of creation. ​ The article highlights the hierarchical nature of the universe, the process of emanation and ascent to the Necessary Being, and the classification of knowledge by Islamic scholars like al-Fārābī and al-Ghazzālī. ​ It advocates for an education system rooted in Tawhidic epistemology to ensure knowledge reflects the true nature of reality, fostering unity, universality, and spiritual understanding. ​